given f(x)=3x-1 and g(x)=2x-3, for which value of x does g(x)=f(2)?

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

given f(x)=3x-1 and g(x)=2x-3, for which value of x does g(x)=f(2)?

Mathematics
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

so we need to figure out what makes g(x) = f(2) so we are given that for f(x) x = 2 so plug in x = 2 into f(x) = 3x-1 and see what number we have.. then we can find an x and plug it into g(x) to make g(x) = f(2) true
so f(x) would = 7
wrong arithmetic. If f(x) = 3x+1 x = 2 f(2) = 3(2)+1=6+1=7 but we are given f(x) = 3x-1 so plug x = 2 in the correct function .

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

so f(2) = 3(2) -1 ? we are subtracting
@tildax what is 6 - 1?
sorry just got back lol and 5 haha
it's alright lol so f(2) = 5 so now we need an x for g(x) to produce 5 g(x) = f(2) g(x) =5
g(x)=2x-3 what x value do we need to produce 5?
4
alright! so when x = 4 g(4) = 2(4)-3 =8-3=5 so g(4) = f(2) 5=5 :)
yay tyty
how do i medal you or what ever for thanks haha
click on best response button
i did :)
yay I got it :)

Not the answer you are looking for?

Search for more explanations.

Ask your own question